156k views
1 vote
Brayden is simplifying the expression 4n – (n – 3)2. He begins by distributing the negative to the terms inside the parentheses. What should he have done instead?

Brayden is simplifying the expression 4n – (n – 3)2. He begins by distributing the-example-1

2 Answers

7 votes

Answer: B. square the binomial

Just took the test on edge, this is correct :)

User Odedbd
by
5.1k points
5 votes

Answer: Square the binomial.


Explanation:

1. The form
(a+b)^(2) indicates that he must square the binomial.

2. By definition, the square of a binomial produces a trinomial, which has the following form:


(a+b)^(2)=a^(2)+2ab+b^(2)\\(a-b)^(2)=a^(2)-2ab+b^(2)

3. Then, you have:


4n-(n-3)^(2)=4n-(n^(2)-2(n)(3)+3^(2))=4n-(n^(2)-6n+9)=4n-n^(2)+6n-9=-n^(2)+10n-9

4. Therefore, the answer is the second option.


User BSeitkazin
by
4.9k points